Teaching and Learning Mathematics in Sub-Saharan Africa: An Introduction to the Special Issue - Räsänen Pekka; Fritz Annemarie; Haase Victor Geraldi (Kaplan Higher Education Academy, 2025)
Before the pandemic, it was estimated that globally six out of ten children and adolescents were not able to read or handle mathematics with proficiency by the time they are of age to complete primary education. That makes over 600 million children and teenagers (56%) whom we fail to teach the basic skills required for an independent adult life (UNESCO Institute for Statistics 2017). One of the areas where this educational challenge is largest is Sub-Saharan Africa. Not only is there a constant challenge to offer quality education for all, but due to population growth, an additional challenge is to train millions of new teachers for the growing school systems. This special issue paints a picture of the current state of mathematics learning and teaching in Sub-Saharan Africa with a focus on both teachers and students.